Teacher learning and learning from teaching - Flores, Maria Assunção (2015)
Teacher learning has attracted a great deal of attention over the last decades. Researchers have sought to shed light on the content, nature, process and outcome of teachers’ learning as well as on their preferences and on the conditions that might foster or hinder their professional growth (Day, 2001; Forte & Flores, 2014; Lieberman, 1996; Meirink, Meijer, Verloop, & Bergen, 2009). Empirical work showed that emancipatory and practical motives to engage in professional development opportunities (e.g. developing oneself and generating a new purpose for teaching) have been identified as more important than policy and instrumental ones (such as implementing government policies and career progression purposes), although the latter has been also recognised as an important factor (Flores et al., 2007; Forte & Flores, 2014).